2015
DOI: 10.1089/cbr.2015.1869
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Gemcitabine Is Nearly Homogenous in Two Orthotopic Murine Models of Pancreatic Cancer

Abstract: Pancreatic cancer is one of the leading causes of cancer-related death in the United States. Gemcitabine is a common treatment, but response rates are low, perhaps due in part to tumor hypoxia. We utilized (14)C-labeled gemcitabine to map distribution of the drug with respect to perfused and hypoxic regions of the tumor microenvironment in two orthotopic xenograft models of pancreatic cancer. There was only a slight reduction in gemcitabine in hypoxic areas, with ∼78% of the drug present in hypoxic compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…There was little activity found in the bulk tumor regions or hypoxic zones. This is in contrast to previous results with AsPC1 tumors [24] where we found gemcitabine to be more evenly distributed throughout the tumor with significant accumulation in hypoxic tissue. However, AsPC1 tumors grow with very little stroma and this may lead to increased drug accessibility.…”
Section: Discussioncontrasting
confidence: 99%
“…There was little activity found in the bulk tumor regions or hypoxic zones. This is in contrast to previous results with AsPC1 tumors [24] where we found gemcitabine to be more evenly distributed throughout the tumor with significant accumulation in hypoxic tissue. However, AsPC1 tumors grow with very little stroma and this may lead to increased drug accessibility.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, overcoming drug resistance has become a critical issue in anticancer therapy. Recent studies have highlighted the role of lipid metabolism in influencing drug resistance (Kramer et al, 2015;Wu et al, 2015;Cotte et al, 2018). It has been shown that lipid-related processes can impact drug efficacy by affecting drug diffusion, altering membrane permeability, influencing mitochondrial function, and modulating the activity of ABC transporter proteins (Hegedüs et al, 2015).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…A recent study demonstrated that LysoPL containing long saturated fatty acyl chains can induce drug resistance. This protective effect of LysoPL enables tumor cells to withstand DNA-damaging agents like cisplatin, representing a lipid-specific and drug-specific protective mechanism (Kramer et al, 2015) (Figure 2).…”
Section: Phospholipid Metabolism and Chemotherapy Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…A remaining concern is whether the applied therapeutic reaches its intended tumor target, a repercussion of a robust self-defense mechanism that tumor cells and the surrounding microenvironment put forth [8]. Uncoupling these complex tissue-drug interactions have been analyzed in the context of overall drug distribution using radiolabeled therapeutics [9,10], mass spectroscopy tissue analysis [11,12] and computational modeling [13,14], however these tools have limited utility for extensive, patient-specific screening assays to inform personalized therapy. Although fluorescent-based assays have been gaining traction [15], a patient-specific screening assay has yet to be developed.…”
Section: Introductionmentioning
confidence: 99%